2018
DOI: 10.1371/journal.pone.0199886
|View full text |Cite
|
Sign up to set email alerts
|

Emotional cues from expressive behavior of women and men with Parkinson’s disease

Abstract: ObjectiveEmotional experience of people with Parkinson’s disease is prone to being misunderstood by observers and even healthcare practitioners, which affects treatment effectiveness and makes clients suffer distress in their social lives. This study was designed to identify reliable emotional cues from expressive behavior in women and men with Parkinson’s disease.MethodVideotaped expressive behavior of 96 participants during an interview of discussing enjoyable events was rated using the Interpersonal Communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…This study suggested that these socially desired behaviours can be misunderstood by observers, even healthcare professionals, and mask negative emotional experiences of women with PD, particularly when smiling and laughing is expressed with less conversational engagement. 43 These findings are in line with the remarks of women in our study that the performance of certain social roles, such as active family care and household duties, can mask experienced difficulties with PD-related symptoms observed by others. Subsequently, this can lead to inaccurate evaluations of emotional and physical well-being of women with PD, intensify feelings of not being listened to or taken seriously and could explain why the women in this study described their need for- and use of more adaptive coping strategies compared to men.…”
Section: Discussionsupporting
confidence: 91%
“…This study suggested that these socially desired behaviours can be misunderstood by observers, even healthcare professionals, and mask negative emotional experiences of women with PD, particularly when smiling and laughing is expressed with less conversational engagement. 43 These findings are in line with the remarks of women in our study that the performance of certain social roles, such as active family care and household duties, can mask experienced difficulties with PD-related symptoms observed by others. Subsequently, this can lead to inaccurate evaluations of emotional and physical well-being of women with PD, intensify feelings of not being listened to or taken seriously and could explain why the women in this study described their need for- and use of more adaptive coping strategies compared to men.…”
Section: Discussionsupporting
confidence: 91%